Anatomical Variations of the Recurrent Laryngeal Nerve and Implications for Injury Prevention During Surgical Procedures of the Neck. Issue 3 (2020) - Fahim, Daniel K.; Thomas, Alison M; Gemechu, Jickssa M
No abstract available